2016
DOI: 10.3389/fnhum.2016.00625
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-Based Step Regularity Is Lower in Older Adults with Bilateral Knee Osteoarthritis

Abstract: Purpose: To compare the regularity and symmetry of gait between a cohort of older adults with bilateral knee osteoarthritis (OA) and an age and sex-matched control group of older adults with healthy knees.Methods: Fifteen (8 females) older adults with knee OA (64.7 ± 6.7 years) and fifteen (8 females) pain-free controls (66.1 ± 10.0 years) completed a 9-min. walk at a self-selected, comfortable speed while wearing a single waist-mounted tri-axial accelerometer. The following gait parameters were compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
(71 reference statements)
2
25
0
1
Order By: Relevance
“…Unlike step symmetry, stride regularity showed no significant difference between patient groups. These results are similar to those of Barden et al 8) . Although Barden et al did not measure leg strength asymmetry, they reported that AP and VT step symmetry values were lower in patients with knee OA than in healthy individuals Step symmetry in the AP, VT, and ML directions were 0.601, 0.675, and 0.588 during normal walking, respectively, and 0.707, 0.761, and 0.590 during Nordic walking, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Unlike step symmetry, stride regularity showed no significant difference between patient groups. These results are similar to those of Barden et al 8) . Although Barden et al did not measure leg strength asymmetry, they reported that AP and VT step symmetry values were lower in patients with knee OA than in healthy individuals Step symmetry in the AP, VT, and ML directions were 0.601, 0.675, and 0.588 during normal walking, respectively, and 0.707, 0.761, and 0.590 during Nordic walking, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Step symmetry values in healthy elderly individuals were reported to be 0.71 35) , 0.77 36) , and 0.86-0.88 8) in the AP direction; 0.72 35) , 0.83 36) , and 0.90-0.92 8) in the VT direction; and 0.49 35) , 0.63 36) , and 0.62-0.75 8) in the medial-lateral (ML) direction. In the present study, step symmetry values in patients with lesser leg strength symmetry were 0.85, 0.87, and 0.61 in the AP, VT, and ML directions, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceleration signal was then aligned with gravity (Moe-Nilssen, 1998) and the direction of motion within the horizontal plane (Avvenuti et al, 2013). The signal was segmented into steps (Lee et al, 2010), each step was normalized to 50 data points, and a previously defined set of 24 features (Moe- Nilssen and Helbostad, 2004;Kobsar et al, 2014;Barden et al, 2016) was extracted from the signal ( Table 2). These features included the peaks, magnitude (RMS), and ratio of the acceleration in three dimensions, averaged across all steps.…”
Section: Data Processingmentioning
confidence: 99%
“…Se puede hacer uso de los acelerómetros para analizar las afecciones espaciotemporales de la marcha en pacientes con osteoartritis de rodilla, enfermedad de Parkinson, adultos mayores. Adicionalmente, con esta medición se pueden detectar asimetrías en cuanto a la velocidad, acho de paso, cadencia y control de tronco que se relacionen con riesgo de caída y alteración del balance en posición estática y dinámica (5,11,12,(42)(43)(44)(45)(46)(47)(48)(49)(50). De hecho, la evaluación a través de acelerometría puede detectar alteraciones en la marcha como perturbaciones, temblores, pasos cortos en pacientes con enfermedad de Parkinson y ser una evaluación objetiva para dirigir tratamientos enfocados en la rehabilitación de estos factores y tener un seguimiento cuantitativo de los resultados del paciente debido a que los acelerómetros permiten evaluar en planos frontal, sagital, transversal detectando alteraciones antero posteriores y laterales (51-57).…”
Section: Análisis De Movimiento Corporal Humanounclassified